2016
DOI: 10.1525/collabra.36
|View full text |Cite
|
Sign up to set email alerts
|

‘Standing in Awe’: The Effects of Awe on Body Perception and the Relation with Absorption

Abstract: The experience of awe is typically elicited in response to perceptually vast stimuli and is often characterized by feeling small and insignificant. In the present series of studies we aimed (1) to determine the effects of awe on body perception and (2) to elucidate the role of the personality trait of 'absorption' (i.e. the tendency to get fully immersed in one's experiences) in relation to the feeling of awe. Across 4 different studies, involving both lab-based and field experiments, we found that feelings of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
68
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 72 publications
(73 citation statements)
references
References 54 publications
3
68
2
Order By: Relevance
“…This study was conducted as a lab-based study. In addition to this study participants also conducted an unrelated study on feelings of awe and the effects on the perception of the self, which are reported elsewhere (van Elk, Karinen, Specker, Stamkou, & Baas, 2016). No additional measures were included beyond the items reported above.…”
Section: Methodsmentioning
confidence: 99%
“…This study was conducted as a lab-based study. In addition to this study participants also conducted an unrelated study on feelings of awe and the effects on the perception of the self, which are reported elsewhere (van Elk, Karinen, Specker, Stamkou, & Baas, 2016). No additional measures were included beyond the items reported above.…”
Section: Methodsmentioning
confidence: 99%
“…As control stimuli we used neutral videos of landscapes and positive videos of funny animals. In a previous behavioral study we found that overall participants reported stronger feelings of awe when allowed to passively watch the video compared to when counting the number of perspective changes (van Elk et al, 2016). To control for the potential confound that systematic differences between the content of the different types of videos would contribute to differences in brain activation between conditions, we manipulated the mindset with which participants were watching the videos.…”
mentioning
confidence: 99%
“…To test our hypothesis, we conducted an fMRI study in which participants were presented with videos of natural phenomena that in previous studies have been used successfully to elicit feelings of awe (Piff et al, 2015;van Elk et al, 2016). As control stimuli we used neutral videos of landscapes and positive videos of funny animals.…”
mentioning
confidence: 99%
See 2 more Smart Citations